Om smeden Anders Karl og hans naturalistiske vildfarelser - Glebe-Møller, Jens (Kirkehistoriske Samlinger, 2007)
In Erik Pontoppidan’s many Collectanea relating to Danish history and church history we find two reports on a certain smith, Anders Carl, who around 1730 caused a considerable stir on the island of Lolland. Anders Carl denied or made fun of several Christian dogmas, including that of the Trinity or of the immortality of the soul. Also he seems to have held rather derogatory views on the secular authorities. Apparently he had followers in his home town but the local clergy managed to get him put on trial for an ecclesiastical court and later, at the intervention of the king, imprisoned in the town of Nakskov. Even after his release from prison, through the intermediary of the bishop, he held on to his »naturalistic and deistic« points of view and died as a »non-believer« in 1733. In the present article the first and hitherto unpublished report of Pontoppidan is transcribed and commented on through means of other contemporary or almost contemporary sources. Altogether, the affair of Anders Carl shows that »The Radical Enlightenment« had its lay followers also in the remoter parts of the Realm of Denmark-Norway.